Vida da Faculdade de Letras (2017-2018) - Faculdade de Letras da Universidade de Coimbra (Documentos, 2018)
From the school year of 2012/2013, all the information that was part of the "Life of the Faculty" section, of Biblos Journal has an autonomous existence in digital format. Because it is considered relevant to preserve this memory and because it is understood that it should not integrate a scientific journal, this publication is created to the party, accessible to the internal and external public, which is hosted on theFaculty of Arts and Humanities website and on the University Press platforms. In this volume, information about the school year of 2017/2018 is gathered.